STABILISASI DIMENSI PADA KAYU TANAMAN KARRI (EUCALYPTUS DIVERSICOLOR) DAN JARRAH (E. MARGINATA) BAGIAN I : ASETILASI Dimensional stabilization on regrowth karri (Eucalyptus diversicolor) and jarrah (E. Marginata) Part I : Acetylation - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1993)
Wood blocks of karri and jarrah  measuring 10 mm (radial) x 25 mm (longitudinal) x  100 mm (tangential) were ovendried for  48 hours at 105°C prior  to treatment.  Acetylation  was carried out in 250 ml- reactor  vessels using a 25  %  (v/v) solution of acetic anhydride in xylene.  Three reaction times, i.e., 8, 16 and 24 hours were used for  each wood type. Treatment results are expressed in terms  of weight gain (VG) and volumetric gain (VG). The ability  of treatment to restrict  dimensional changes is expressed as anti swelling efficiency (ASE). Results showed that the weight and volume of both eucalypts specimens substantially increased after acety- lation. In all cases, karri specimens showed higher weight gain, volumetric gain and ASE than jarrah.  The effectiveness of acetylation increased with increases in reaction time. Volumetric swelling reduction of more thaw 80% was found in the two regrowth eucalvots.